Mahasiswa Dan Realitas Kuliah Online (Analisis Persepsi Mahasiswa di Ruang Teks Opini Media) - Launa Launa; Bambang Mudjiyanto; Ari Cahyo Nugroho; Felix Tawaang; Hayu Lusianawati (Universitas Bina Sarana Informatika, 2022)
Abstract. Since the Covid-19 pandemic broke out in March 2019, online lectures or online learning modes have been established by the government through the Directorate General of Higher Education Circular Number 1 of 2020 concerning Prevention of the Spread of Covid-19 as a learning system that must be used at all levels of education units, including universities. The implementation of online lectures at universities not only raises positive opinions, but also negative perceptions of students, as reflected in student opinions whose opinions are presented in the online media news portal room. This study aims to analyze the negative views of students whose sources are extracted from opinion texts on the sample online media news portal page. This qualitative study with descriptive-interpretative analysis method seeks to analyze student opinion texts at the level of their perception, attention, interpretation, and response to the online lectures they have been attending. The results of the study show: This study aims to analyze the negative views of students whose sources are extracted from opinion texts on the sample online media news portal page